Vulnerabilities and Legal Protection: Exploring Islamic Family Law in Malaysia (Kanun: Jurnal Undang-undang Malaysia, 2024)
Islamic family law has significant impact on the personal lives of Muslims, as it establishes and protects the formation of a legal family and defines the rights and responsibilities of family members in various circumstances. This study focuses on the socio-legal perspective of Islamic family law in Malaysia, aiming to explain how the law can protect and empower vulnerable individuals within the family. The discussion begins with a definition of vulnerability and goes on to debate the factors that influence vulnerability within the context of family and marriage. The study explores the dynamic aspects of vulnerability and highlights the factors that worsen the situation for vulnerable groups. The main focus is on analysing the role of Islamic family law in reducing the vulnerability of individuals within the family unit. This study employs a qualitative approach, utilising literature review and descriptive analysis. By analysing the empowerment of vulnerable individuals, the research emphasises the priority of preserving the welfare and well-being of the family, which, in turn, strengthens the community and society.Keywords: Islamic family law, protection of the vulnerable, empowerment of the vulnerable, access to justice, marriage registration, child protectionFull text: PDF